Pityriasis Rosea and Immunosuppressive Drugs [Response to Letter] - Wu H; Ji QJ; Xu YY; Zhu JW (Clinical, Cosmetic and Investigational Dermatology, 2024)
Hao Wu, Qing-Jie Ji, Yu-Yang Xu, Jian-Wei Zhu Department of Dermatology, Quzhou TCM Hospital at the Junction of Four Provinces Affiliated to Zhejiang Chinese Medical University, Quzhou, People’s Republic of ChinaCorrespondence: Jian-Wei Zhu, Email zjwmed@163.com